Image-i-nation and fictocriticism: rewriting of the Malay myth. - Nasirin Abdillah (2016)
The premise of this study centres upon the examination of rewriting the Malay myth in a critical and creative context.The main focus is on the way myth rewriting can reconfigure the notion of ‘nation’.In the scholarly component of this thesis,two of Fatimah Busu’s short stories,“Al-Isra” (“Night Journey”) and “Gurindam Jiwa 50 Tahun Merdeka” (“S50 Years of Independence:A Gurindam Jiwa”) are the main materials for analysis.Fatimah Busu’s works has been chosen as she primarily and consistently draws upon the idea of myth rewriting in many of her short stories.I intentionally chose these two particular short stories because they are referential to the two main Grand Narratives in Traditional Malay Literature:Hikayat Hang Tuah (Story of Hang Tuah) and Sulalat al-Salatin (Genealogies of the Sultans/Kings).“Al-Isra’ is based on Hikayat Hang Tuah whilst “Gurindam Jiwa 50 Tahun Merdeka” is based on Sulalat al-Salatin,respectively.This thesis uses the theoretical framework of mythology to support the textual analysis and a close-reading approach.In this study,I propose the concept of ‘image-i-nation’.This concept is loosely taken from the word,‘imagination’ from which I have broken down into three words:image,I and nation.This is my way of offering a new critical analysis in investigating myth in the context of rewriting.The central argument in the concept is that myth,as I believe,originates in the collective consciousness of human imagination,then it is translated into tales and later is reproduced in various forms that has its origins in oral traditions,leading to the writing system and culminating in cinematic expressions.In the retelling of myth,I proffer that the tale retold carries within it,consciously or unconsciously,“image(s)” of the self/individual (“I") and the other/society (“nation”).Furthermore,this concept aims at opening up discussions on the nation as delineated in the socio-cultural,political and historical contexts of Malaysia.The creative component of the thesis will also deal with the idea of myth rewriting.The notion of nation will serve as the main theme in which the creative work will explore this notion using the genre of fictocriticism.The creative component consists of a collection of micro-fictocritical writings that addresses issues pertinent to the nation by focusing on issues such as identity, self and other.Fictocriticism produces a dual narrative:one,which employs a fictional voice and the other,a critical voice.The critical voice in the format of fictocriticism is dominant in the narrative and allows for further personal commentaries on the negotiation between self and the other as seen in relation to the notion of nation.The use of fictocriticism further helps to explore how myth can be exploited to expand the notion of nation as explicated in the relationship between the self and the other.The use of myth in new writing and contemporary setting may engender a wide spectrum of new meanings and interpretations.It is hoped that the inclusion of the concept of ‘image-I-nation’ in this research and the use of fictocriticism in the creative component may contribute to the development of a new ‘way’ of approaching or looking at the Malay myths.